DIGITAL TRANSFORMATION IN EDUCATION: A SOCIOLOGICAL LITERATURE REVIEW ON TECHNOLOGY, INEQUALITY, AND SOCIAL CHANGE - Hikmat (GoAcademica Research dan Publishing, 2024)
Digital transformation has profoundly reshaped the landscape of education, creating both opportunities and challenges that demand critical sociological inquiry. This article employs a literature review methodology to synthesize existing research on the intersection of technology, inequality, and social change in educational contexts. The review highlights that while digital tools enhance access to knowledge and innovative learning models, they also exacerbate persistent inequalities rooted in socioeconomic status, geography, and institutional capacity. Studies consistently reveal that the digital divide reinforces structural disadvantages, limiting the benefits of technology for marginalized groups. The sociological perspective emphasizes how technology is not merely a neutral instrument but a socially embedded phenomenon that reflects power relations and cultural dynamics. Literature further indicates that digital transformation in education contributes to broader processes of social change, including shifts in teacher–student relationships, institutional norms, and labor market demands. At the same time, findings underscore the role of policy frameworks and governance structures in mediating the equitable adoption of digital education. The analysis also points to the importance of integrating sociological theories to interpret the contradictions between technological promise and lived realities. By critically engaging with prior studies, this review reveals both progress and persistent challenges in creating inclusive digital education systems. Ultimately, the article contributes to scholarly debates by framing digital transformation in education as a multifaceted social phenomenon rather than a purely technological advancement.